Lebanon's Political Economy of Informality: Elites, Citizens and the State Shape Money(s) during the Sovereign Debt Crisis - Helou, Joseph P. (2021)
This chapter contributes to the literature on divided societies by examining why Lebanon’s sovereign debt crisis of 2020, with a sectarian political order, elite power sharing arrangements and fragmented state institutions as a backdrop, bred market dynamics that accommodated a set of economic and financial informality. It examines citizens’ embracement of the informal practices of bankers’ check conversions to cash Dollars, jewelry, or property at a discount, while analyzing the behavior of elites’ manipulation of markets where the existence of multiple exchange rates helps them achieve a political rebound. It argues that citizens’ embracement of economic informality helps them contest elite practices and sectarian state institutions, whereas conditions on volatile markets –occurring in fluid governance spaces where multiple actors shape practices– also enable elites’ manipulation of market exchange rates, imposition of an unspoken haircut on deposits, removal of subsidies that favor vulnerable segments and the settlement of scores with their political counterparts. It finds that state failures – epitomized in consistently negative balance of payments, currency inflation and an inability to provision credit, collect taxes and spend on infrastructural projects– can be ameliorated with a renewed outlook on the politics of money. This politics of money should spawn genuine economic spaces where citizens’ participation in political, economic, and social fields –without elite intervention– create opportunities for economic growth. It suggests measures to achieve a positive balance of payments, starting with a competition law, set of comprehensive political reforms, international assistance and an economic plan for currency stabilization and investments in the country’s productive sectors.